PEMBUATAN GRASSLAND EDUACATION CENTER FAKULTAS PETERNAKAN UNIVERSITAS WIJAYA KUSUMA PURWOKERTO (WIKUACITYA: Jurnal Pengabdian Kepada Masyarakat, 2023)
Community service activities for the creation of the Grassland Education Center aim to provide adequate forage laboratory facilities to provide practical training to students and encourage students to be involved in research and community service. Activities in the form of land management and planting forage and fodder grass are carried out on vacant land behind the Unwiku Faculty of Animal Husbandry. The Land Education Center is expected to improve the quality of education and research by providing a place for student practicum. being a point of collaboration between the faculty and the local livestock industry, acting as a center for community education, and being expected to be an important asset for promoting the Faculty of Animal Husbandry and Unwiku as a whole.